Sweat Bees, Halictid Bees, Halictidae (Insecta: Hymenoptera: Halictidae) - Katie Buckley; Catherine Zettel Nalen; Jamie D. Ellis (EDIS)
Sweat bees are very important pollinators for many wildflowers and crops, including stone fruits, pomme fruits, alfalfa, and sunflower. Sweat bee populations can be encouraged with wildflower plantings and by providing nesting areas. Halictids typically nest in bare soil located in a sunny location. Minimum tillage and insecticide use will help to increase populations of Halictidae and other soil nesting bees. Learn more about this diverse family of bees in this 5-page fact sheet was written by Katie Buckley, Catherine Zettel Nalen, and Jamie Ellis, and published by the UF Department of Entomology and Nematology, August 2011.